Analisis Efisiensi Kinerja Kolam Stabilisasi pada Instalasi Pengolahan Air Limbah Domestik Bojongsoang Kabupaten Bandung, Jawa Barat - Fanny Novia; Erika Herliana; Jeni Saepurrohman (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Stabilisation ponds are a type of domestic wastewater treatment widely used in tropical and developing countries. One of the domestic wastewater treatment plants (IPAL) using a stabilisation pond is the Bojongsoang WWTP located in Bandung Regency, West Java. The stabilisation pond at Bojongsoang WWTP consists of 2 sets, each of which is a series of 3 anaerobic ponds, 2 facultative ponds and 1 maturation pond. This research aims to analyse the performance of the stabilisation pond at Bojongsoang WWTP in set A. The parameters to be analysed are Biochemical Oxygen Demand (BOD), Total Suspended Solids (TSS) and Ammonia. The data used are secondary data consisting of monthly domestic wastewater quality monitoring data from 2019-2022. The efficiency of BOD removal in 2019-2022 was 70.33%, 79.67%, 84.00 and 84.95%. The efficiency of TSS removal in 2019-2022 was 72.47%; 79.03%; 87.23%; and 79.05%. Meanwhile, the efficiency of ammonia removal in 2019-2022 was 67.95%; 81.71%; 80.06% and 64.53%. The best BOD and TSS removal occurred in anaerobic ponds, while the best ammonia removal occurred in maturation ponds.